2022
DOI: 10.3390/jcm11051429
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer Transformation following Treatment in EGFR-Mutated Non-Small Cell Lung Cancer

Abstract: EGFR-mutated lung adenocarcinoma patients who received tyrosine kinase inhibitors (TKIs) may initially respond to therapy, but over time, resistance eventually occurs. In a small population (5–10%), these patients can have a histological transformation to SCLC. Nine patients with EGFR-mutated lung adenocarcinoma who transformed to SCLC were evaluated at City of Hope. Patient clinical and pathology data, including multiple next-generation sequencing (NGS) results, clinical therapies, histology, and outcomes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…3) harbored only gene alterations of TP53 but without RB1 loss. These ndings indicate that RB1 loss and TP53 mutation are not universally present in transformed SCLC patients, which has also been con rmed by others (Mambetsariev et al 2022;Yu et al 2022). Additionally, PIK3CA mutation was found in 20% of the patients, and BRAF mutation occurred in 10% of the patients, suggesting the molecular heterogeneity of transformation from LUAD to SCLC.…”
Section: Discussionsupporting
confidence: 81%
“…3) harbored only gene alterations of TP53 but without RB1 loss. These ndings indicate that RB1 loss and TP53 mutation are not universally present in transformed SCLC patients, which has also been con rmed by others (Mambetsariev et al 2022;Yu et al 2022). Additionally, PIK3CA mutation was found in 20% of the patients, and BRAF mutation occurred in 10% of the patients, suggesting the molecular heterogeneity of transformation from LUAD to SCLC.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with EGFR exon 19 deletion are also more likely to undergo transformation (26). Another study confirmed that the risk of SCLC transformation is six times higher in patients with concurrent EGFR, TP53, and RB1 mutations than in patients without mutations (25). Moreover, Achaete-scute homolog 1 (ASCL1) can interact with the Rb-p53 (by RB1, TP53 code, respectively) axis to promote the growth of adenocarcinoma with a higher degree of invasion (32).…”
Section: Discussionmentioning
confidence: 94%
“…Histological transformation of EGFR -mutated adenocarcinoma to SCLC was first reported in 2006 as a relatively rare mechanism of resistance ( 2 ). Among patients treated with EGFR-TKIs as targeted therapy, this mechanism accounts for 3-15% of transformation to SCLC, particularly transformation from adenocarcinoma to SCLC ( 25 ), which may constitute a potential mechanism of acquired drug resistance to EGFR-TKIs ( 26 ). Small cell transformation as a resistance mechanism for immunotherapy was first reported in 2017 by Imakita et al.…”
Section: Discussionmentioning
confidence: 99%
“…The transformation from NSCLC to SCLC is a mechanism of resistance to EGFR‐TKIs 13,14 . Marcoux et al investigated the clinical outcomes of EGFR ‐mutated lung adenocarcinomas transforming to SCLC, showing that the median OS since the time of SCLC transformation was 10.9 months, 15 whereas another report described long‐term survival with an OS of 58 months from SCLC transformation 16 . In comparison with these reports, our patient survived for more than 142 months from the initial diagnosis of SCLC transformation, which may be partly attributed to repeated salvage surgeries and stereotactic radiotherapy along with systemic therapies.…”
Section: Discussionmentioning
confidence: 99%